Gamma irradiation of common beans: Effect on nutritional and technological properties - Carvalho Lima, Dâmaris (2019)
ABSTRACT This work aimed studied the effect of ionizing irradiation on the nutritional and technological properties of cooked Carioca beans (Phaseolus vulgaris). The dry beans were irradiated with different doses (1, 5 and 10 kGy) of γ-radiation using 60Co as source. The composition and nutritional properties (protein, fat, ash, tannin, phytic acid content and protein in vitro digestibility) of the cooked beans were analyzed, with and without previously soaking process. In addition, the technological properties (hydration index, cooking time and color) of the beans were also evaluated. The results showed that protein, fat, ash and tannin content, as well as color, were not affected by irradiation, while the phytic acid was significantly reduced by the irradiation. Further, hydration index was slightly reduced only by using 10 kGy suggesting probable structure changes. Irradiation reduced the cooking time of the beans, as higher irradiation doses were used, which was related with the reduction on the phytic acid content. Moreover, protein in vitro digestibility was enhanced by irradiation. In conclusion, irradiation up to 10 kGy can be safely used to improve the shelf life of common beans without degradation of nutritional components, reducing some antinutrients content, improving protein digestibility and reducing the cooking time.